ANALISIS KUALITAS MUTU DAN INOVASI PRODUK SERTA PERAN BRAND IMAGE DALAM MENINGKATKAN DAYA SAING BISNIS SERTA DAMPAK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DAN PERKEMBANGAN USAHA UMKM ROTI ARIMBI DI PEKON TULUNGAGUNG TAHUN 2020 - Indra Jaya; Indra Budi Sumantoro (Bajang Institute, 2022)
Business in the economic field can be said to be an activity carried out by every entrepreneur or individual for the purpose of making a profit. Businesses can also function to create products with new innovations to increase economic growth so as to create consumer purchasing decisions. MSMEs are labor-intensive businesses that use local raw materials, and as providers of goods and services for the community's basic needs. MSME Roti Arimbi as a place of research, MSME Roti Arimbi is one of the MSMEs in Pekon Tulungagung, Gadingrejo sub-district and is engaged in the packaged bread business. The problem of this research is that purchasing decisions have increased and the business development of the Arimbi Roti MSMEs has grown significantly from year to year, there is an increase. The purpose of this study was to find out the quality of product quality and innovation as well as the role of brand image in increasing business competitiveness and the impact on consumer purchasing decisions and the business development of Arimbi Roti MSMEs in Pekon Tulungagung in 2020. This research is a descriptive study using a qualitative descriptive approach. The data used are primary data obtained through observation and interviews. In this method, direct interviews with the object of research were observed, namely the owners of Arimbi Roti MSMEs and stalls that do Arimbi Roti product agency. The data analysis method in this study is a qualitative method with the help of the NVivo 12 Pro program. Based on the results of data analysis using the NVivo 12 Pro program, overall all the variables in this study have been declared good